PENGARUH KOMPETENSI SUPERVISI KEPALA MADRASAH TERHADAP PROFESIONALISME GURU - Purwantini; Abdul Rouf; Adibah (FAI- Undar, 2017)
The purpose of this research is testing the influence supervision competence on Profesionalism among teachers at Islamic Basic School of Miftahul Khoirot Sambirejo Geger Kabupaten Madiun.Design of this research is a quantitative research because testing the contribution between two variable there is independent variable (supervision) and dependent variable (profesionalism). Collecting data methods using questionnaire which is given to all the teachers in Islamic Basic School of Miftahul Khoirot as the respondents than it is analyzed using simple regression and proceed with 17th version of SPSS software. The population and sample in this research is all the teachers in Islamic Basic School of Miftahul Khoirot about 17 teachers, because the population is less than 100 in its account, then the sample is taken from that population.The results of this study indicate that: (1) There is significant influence (0,00<0,01) Supervision competence on profesionalism among teachers in Islamic Basic School of Miftahul Khoirot accounted for 95% (2) regression coefficient of 1.865 means that any increase of supervision competence will be followed by an increase in teachers professionalism Islamic Basic School of Miftahul Khoirot Sambirejo. through regression equation : Y = 30.672 + 1.865 X